A study on torque ripple improvement compared to a modified rotor and stator poles SRMs with classical SRMs using dynamic and FFT analysis - TERZİ, ÜMİT KEMALETTİN (My University, 2023)
SRMs have high torque ripples. Modifying the stator and rotor shape of SRMs is one of their methods to remove torque ripples. In this study, new rotor and stator geometries have been proposed for SRM. Performance characteristics are obtained and dynamic analyses are carried out for both novel and classical 6/4 SRMs. FFT analyses of the torque characteristics are also performed for the both SRMs. The changes in performance and the FFT results of torque characteristics are determined for both the current-controlled and uncontrolled operations in both SRMs. 23.60% and 15.20% improvements in torque ripples are achieved for the uncontrolled and current-controlled operations in SRMs respectively. When the FFT analyses are applied to the torque characteristics, the THD values are obtained as 21.19% and 8.31% in the uncontrolled and controlled motor current operations respectively. A 122 W three-phase 6/4 SRM simulation based on the MATLAB–SIMULINK environment is performed to validate the improvement of the torque ripple of the proposed model.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; Enerji Mühendisliği ve Güç Teknolojisi; Fizik Bilimleri; Makine Mühendisliği; Elektrik ve Elektronik Mühendisliği; Energy Engineering and Power Technology; Physical Sciences; Mechanical Engineering; Electrical and Electronic Engineering; FFT analysis; switched reluctance motor; torque ripple reduction